Changes in IGFBP-2 levels following a one-year lifestyle modification program are independently related to improvements in plasma apo B and LDL apo B levels. (February 2019) - Carter, Sophie; Lemieux, Isabelle; Li, Zhuo; Alméras, Natalie; Tremblay, Angelo; Bergeron, Jean; Poirier, Paul; Després, Jean-Pierre; Picard, Frédéric
Abstract: Background and aims: Recent transversal studies have associated insulin-like growth factor binding protein (IGFBP)-2 levels with glucose tolerance and parameters of the lipoprotein-lipid profile. Here, we aimed at determining the longitudinal effects of a one-year lifestyle modification program on IGFBP-2 levels and to identify specific metabolic improvements impacted by the changes in IGFBP-2. Methods: 99 middle-aged Caucasian men were involved in a lifestyle modification program consisting in personalized healthy eating and physical activity counseling, combined to elicit a daily 500 kcal deficit. Anthropometric and metabolic parameters as well as circulating IGFBP-2 levels were measured before and after one year of the lifestyle modification program. Results: The intervention triggered positive changes in many metabolic parameters and a 43% ( p <  0.0001) increase of IGFBP-2 levels. Subjects with the most substantial increases in IGFBP-2 also experienced the most important metabolic improvements. Changes in IGFBP-2 levels (both absolute and relative) were correlated with markers of body fat distribution and lipoprotein-lipid profile, and independently associated with changes in LDL apolipoprotein (apo) B but not VLDL apo B concentrations. Further analyses showed that for similar changes in BMI, waist circumference and visceral adipose tissue volume, large changes in IGFBP-2 levels were required to observe improvements in LDL apo B levels. Conclusions: The 1-year lifestyle modification program was associated with increased IGFBP-2 concentrations. Increases in IGFBP-2 levels were closely associated with reduced LDL apo B concentrations and independently of the modifications in fat mass and insulin sensitivity. Further mechanistic studies are required to assess the effects of IGFBP-2 levels on LDL metabolism. Graphical abstract: Image 1 Highlights: A 1-year lifestyle modification program increased circulating IGFBP-2 levels by 43% in men. Changes in IGFBP-2 levels contributed to improvements in plasma apo B. This association was independent from those between IGFBP-2, insulin resistance, and fat mass.